Strategic Approaches for Effective Teaching of Entrepreneurship in Tertiary Institutions of Kano State, Nigeria - Kumazhege, Stephen Z.; G, Usman A.; O, Egunsola A.; Ibanga, Isaac John (EDUMALSYS Journal of Research in Education Management, 2024)
This study determined the strategic approaches for effective teaching of entrepreneurship in tertiary institutions of Kano State, Nigeria. The study was guided by two specific objectives; two research question and two null hypotheses tested at 0.05 levels of significance. Survey research design was adopted for the study. The study was conducted in five tertiary institutions of Kano State, Nigeria. The population of the study was 32 lecturers, consisting 14 from university, 15 from colleges of education and 3 from Polytechnic. The study adopted census sampling technique because the whole population was used as a sample. Instrument for data collection was a structured questionnaire developed by the researcher title; Strategies for Stimulating Entrepreneurship Among Automobile Technology Education Students Questionnaire (SSEAATESQ). Cronbach alpha was used to determine the reliability coefficient of the instrument which was 0.977. The data collected for this study were analyzed using mean and standard deviation for answering the research questions. ANOVA was used to test the null hypotheses at 0.05 levels of significance. Use of consumable instructional material, serve as strategy to stimulate effective teaching and learning of entrepreneurship education in tertiary institutions of Kano State. An internship can provide an opportunity for students, Collaboration with industry partners can provide valuable opportunities for interns to work on real-world entrepreneurial projects. The federal government in collaboration with state governments should provide Innovation labs equipped with tools, technologies, and resources for students to experiment, prototype, and develop their entrepreneurial ideas by way of encouragement. Collaboration between tertiary institutions and industries should be used as a strategy to strengthen in the area of student’s practical work experience.